1991
DOI: 10.1111/j.1464-5491.1991.tb01582.x
|View full text |Cite
|
Sign up to set email alerts
|

Birthweight of Babies Born to Mothers with Type 1 Diabetes: is it Related to Blood Glucose Control in the First Trimester?

Abstract: A retrospective study of 133 pregnancies in women with Type 1 diabetes was performed, and the 116 which progressed beyond 28 weeks were further analysed. Despite good maternal blood glucose control (mean (+/- SE) HbA1 levels 8.6 +/- 0.2% at the end of the first trimester; 6.9 +/- 0.2% at delivery; normal range 4.0-8.5%), 38% of babies had birthweights above the 90th centile and operative intervention occurred in 77 deliveries (66%). There was no significant correlation between birthweight and HbA1 level at any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 25 publications
2
14
0
1
Order By: Relevance
“…Even with maternal glucose levels in the normal range, the higher the ambient glucose during the last trimester of pregnancy, the heavier the baby at birth. These results are consistent with data from other populations, in mothers who have pre‐existing diabetes [8–14] and with all the studies of maternal glucose levels and fetal growth in non‐diabetic populations [16–18].…”
Section: Discussionsupporting
confidence: 92%
“…Even with maternal glucose levels in the normal range, the higher the ambient glucose during the last trimester of pregnancy, the heavier the baby at birth. These results are consistent with data from other populations, in mothers who have pre‐existing diabetes [8–14] and with all the studies of maternal glucose levels and fetal growth in non‐diabetic populations [16–18].…”
Section: Discussionsupporting
confidence: 92%
“…[14][15][16][17] There is, however, no agreement about which maternal glucose measure temporally related to meals is a better predictor of macrosomia. Although some [15][16][17][18][19] have found that the postmeal glucose and/or hemoglobin A1 are the best predictors, others 14 have reported that a fasting glucose taken from 29 to 32 weeks is a better predictor than postprandial measures.…”
Section: Maternal Glycemiamentioning
confidence: 99%
“…However, despite improved glycaemic control over the past decade, the incidence of macrosomia is still very high (27-43%) and does not seem to decline [1,4,5,14,15,16,17]. When trying to reduce macrosomia in Type I diabetic pregnancies, it would be useful to know the characteristics of women with the highest risk for having a macrosomic infant.…”
mentioning
confidence: 99%